2017
DOI: 10.1242/jcs.194241
|View full text |Cite
|
Sign up to set email alerts
|

Sideroflexin 3 is an α-synuclein-dependent mitochondrial protein that regulates synaptic morphology

Abstract: ABSTRACTα-Synuclein plays a central role in Parkinson's disease, where it contributes to the vulnerability of synapses to degeneration. However, the downstream mechanisms through which α-synuclein controls synaptic stability and degeneration are not fully understood. Here, comparative proteomics on synapses isolated from α-synuclein−/− mouse brain identified mitochondrial proteins as primary targets of α-synuclein, revealing 37 mitochondrial proteins not previously linked to α-synuclein or neurodegeneration pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 31 publications
3
41
0
Order By: Relevance
“…Instead, the transmembrane domains of SFXN2 functioned as a mitochondrial targeting signal and guided SFXN2 to the mitochondria. In contrast to SFXN2, SFXN3, and SFXN4 are targeted to the inner mitochondrial membrane [ 33 , 34 ]. Sequence homology is 54% between SFXN2 and SFXN3, but only 20% between SFXN2 and SFXN4 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, the transmembrane domains of SFXN2 functioned as a mitochondrial targeting signal and guided SFXN2 to the mitochondria. In contrast to SFXN2, SFXN3, and SFXN4 are targeted to the inner mitochondrial membrane [ 33 , 34 ]. Sequence homology is 54% between SFXN2 and SFXN3, but only 20% between SFXN2 and SFXN4 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although the molecular functions of Sfxn proteins are unclear, recent studies demonstrated that these proteins are involved in physiological functions and disease. For example, Sfxn3 has been implicated in the differentiation of pancreatic islets in mice and the regulation of synaptic morphology at neuromuscular junctions in Drosophila [ 32 , 33 ]. Pathogenic mutations of the SFXN4 gene have been identified in mitochondrial disease patients with macrocytic anemia [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Proteomics analysis identified a series of α-syn interactors at the level of the IMM, including mitofilin, a mitochondrial inner membrane protein important for the regulation of cristae morphology ( John et al, 2005 ; McFarland et al, 2008 ). iTRAQ proteomics on synaptosomes from α-syn +/+ and α-syn -/- mice also revealed that α-syn interacts with sideroflexin 3 (SFXN3), a putative iron transporter of the IMM ( Fleming et al, 2001 ; Li et al, 2010 ) which is important for maintenance of the synaptic morphology and neuromuscular junctions ( Amorim et al, 2017 ) and that has been found down-regulated in substantia nigra of PD-affected patients ( Simunovic et al, 2009 ).…”
Section: Mitochondrial Routes For Alpha-synucleinmentioning
confidence: 99%
“…Sfxn5 expression is high throughout the adult human brain compared to other tissues (Lockhart et al 2002). A developmental role for Sfxn3 is suggested from a study showing that Drosophila Sfxn3 mutants exhibit abnormal synaptic morphogenesis at the neuromuscular junction (Amorim et al 2017). Interestingly, Sfxn3 is a downstream target of α-synuclein, and may be involved in the neurodegenerative process in Parkinson’s disease (Amorim et al 2017).…”
Section: Introductionmentioning
confidence: 99%